Pervasive Computing 7th International Conference, Pervasive 2009, Nara, Japan, May 11-14, 2009, Proceedings - Tokuda, Hideyuki; Beigl, Michael; Friday, Adrian; Brush, A. J. Bernheim; Tobe, Yoshito (Information Systems and Applications, incl. Internet/Web, and HCI, 2009)
This book constitutes the refereed proceedings of the 7th International Conference on Pervasive Computing, Pervasive 2009, held in Nara, Japan, in May 2009. The 20 revised full papers and 7 revised short papers presented were carefully reviewed and selected from 147 initial submissions. The papers are organized in topical sections on digital displays, navigation, at home with pervasive applications, sensors, sensors, everywhere, working together, tagging and tracking, methods and tools, and the importance of context.